LINGUOPOETIC ACTUALIZATION OF UNUSUAL COMBINATIONS (International journal of artificial intelligence, 2025)
This article lists the main units of expressive syntax in linguistics. Language levels expressing syntactic expressiveness, including unusual combinations, their role in expressive syntax, and the fact that they are a means of increasing the linguopoetic value of an artistic text are explained. Examples of unusual combinations found in works of art are presented and their linguopoetic features are revealed. It is shown that syntactic structure features have a special place in the study of text construction of unusual combinations.